Visibility and citation impact - Ale Ebrahim, N.; Salehi, H.; Embi, M.A.; Habibi Tanha, F.; Gholizadeh, H.; Motahar, S.M. (Canadian Center of Science and Education, 2014)
The number of publications is the first criteria for assessing a researcher output. However, the main measurement for author productivity is the number of citations, and citations are typically related to the paper's visibility. In this paper, the relationship between article visibility and the number of citations is investigated. A case study of two researchers who are using publication marketing tools confirmed that the article visibility will greatly improve the citation impact. Some strategies to make the publications available to a larger audience have been presented at the end of this paper.